FGFR Inhibitor Toxicity and Efficacy in Cholangiocarcinoma: Multicenter Single-Institution Cohort Experience. (2021) - Gile, Jennifer J.; Ou, Fang-Shu; Mahipal, Amit; Larson, Joseph J.; Mody, Kabir; Jin, Zhaohui; Hubbard, Joleen; Halfdanarson, Thorvardur; Alberts, Steven R.; Jatoi, Aminah; McWilliams, Robert R.; Ma, Wen Wee; et al.
Abstract : PURPOSE: Cholangiocarcinomas (CCA) are a group of heterogeneous tumors arising from the biliary epithelia. Significant sequencing efforts have provided further insights into the molecular mechanisms of this disease including fibroblast growth factor receptor ( FGFR ) alterations, which occurs in approximately 15%-20% of intrahepatic CCAs. Herein, we describe the FGFR inhibitor (FGFRi)-associated treatment toxicity and cancer-specific outcomes from a multicenter single-institution cohort. METHODS: This is a retrospective study of patients with CCA and known FGFR alterations treated with FGFRi. We describe the toxicity and efficacy in patients treated at Mayo Clinic between January 2010 and December 2020. RESULTS: Our group identified 61 patients with advanced or metastatic CCA, 19 males (31%) and 42 females (69%), harboring FGFR alterations who received FGFRi. The most common grade 1 or higher adverse events for all patients included fatigue (92%), AST elevations (78%), anemia (80%), decreased platelet count (63%), and hyperphosphatemia (74%). Median progression-free survival on FGFRi was 5.8 months for all patients (95% CI, 4.9 to 9.0). Females had significantly longer progression-free survival at 6.9 months (95% CI, 5.2 to 11.8) on FGFRi compared with males at 4.9 months (95% CI, 2.8 to not estimable; P = .038). CONCLUSION: FGFRi are well tolerated with clinical efficacy. With the recent approval of FGFRi by the US Food and Drug Administration and ongoing clinical trials for new FGFRi, understanding outcomes and toxicity associated with these medications is important for precision oncology.